Local propagation of visual stimuli in focus of attention - Faggi, Lapo; Betti, Alessandro; Zanca, Dario; Melacci, Stefano; Gori, Marco (Neurocomputing, 2023)
Fast reactions to changes in the surrounding visual environment require efficient attention mechanisms to reallocate computational resources to the most relevant locations in the visual field. In this paper, we present a biologically-plausible computational model of focus of attention that exhibits spatiotemporal locality and that is very well-suited for parallel and distributed implementations. Attention emerges as a wave propagation process originated by visual stimuli corresponding to details and motion information. The resulting field obeys the principle of “inhibition of return” so as not to get stuck in potential holes. The proposed model is obtained as a hyperbolic regularization of the Poisson equation to which it reduces in the limit of high speed of propagation. According to the MultiMatch algorithm for scanpaths comparison, the proposed model achieves very competitive results when considering dynamical input stimuli.
CRIS-Team Scopus Importer:2023-10-13
Keywords: Computer vision; Saliency; Scanpath prediction; Visual attention